THE KNOWLEDGE, ATTITUDES, AND PRACTICES OF LIVESTOCK DEALERS IN WASIT PROVINCE, IRAQ REGARDING ZOONOTIC INFECTIONS - Ali Mazahem Shanjar (Journal of Medical Genetics and Clinical Biology, 2024)
This study aims to determine the knowledge, attitudes, and practices about diseases transmitted to humans from animals. The sample of the study is 77 persons working as breeders, fatteners, and sellers of cows and sheep in the countryside of wasit, Iraq. Those people answered some sociodemographic questions in addition to another three kinds of questions (knowledge attitudes and practices), the level score of knowledge was calculated by giving one point to every question. Participants were 72, and their average age was 45 years. The respondents whom had previously been infected were %87.6% of the respondents, however, 58.6% did not know that they infected from a healthy animal. Only 12.6% of the respondents received training on animal husbandry. The participants who had agricultural education were 37.6% of the participants. Those who know un-boiled milk can transmitted diseases were %65 of the and 96% of whom used to consume un-boiled milk. In this study, the lifetime prevalence of contracting diseases from animals was found to be 5.6%. Wearing gloves 36.2% while only % 28 of the participants was wearing masks. Who did not use any personal protective equipment were %13. Using raw milk was common among those who did not know that raw milk would be infected (p = 0.02). The participants were well informed about the disease transmitted from animals but they had less knowledge that poultry was also a source of infection (P <0.001). Participants do not demonstrate simple personal protective behaviour. Zoonotic diseases can be effectively addressed through the practice of occupational pathology, regional protection, the necessity of using personal protective equipment, and participation in training, especially in how to use it.